1972
DOI: 10.1002/recl.19720911102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the antioxidant action of dialkyl sulfoxides

Abstract: The main inhibiting action of dialkyl sulfoxides in the autoxidation of hydrocarbons derives from their ability to form sulfenic acids on thermal decomposition. The sulfenic acids are extremely active radical scavengers, the rate constant of the reaction of sulfenic acid and peroxy radicals being at least 107 l.mole−1 · S−1 at 60°C. In the AIBN‐initiated oxidation of tetralin in the presence of sulfoxides one peroxy radical is scavenged per molecule of sulfenic acid. This inhibition can be described kineticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 4 publications
4
16
0
Order By: Relevance
“…This result implies that the corresponding TSs are slightly lower in energy than the separated reactants. These reactions are, therefore, predicted to be diffusion-controlled, consistent with Koelewijn and Bergers estimate [10] that the rate constant for the reaction of 2-methyl-2-propanesulfenic acid with [a] Determined from a common hydrogen-bonded prereaction complex.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…This result implies that the corresponding TSs are slightly lower in energy than the separated reactants. These reactions are, therefore, predicted to be diffusion-controlled, consistent with Koelewijn and Bergers estimate [10] that the rate constant for the reaction of 2-methyl-2-propanesulfenic acid with [a] Determined from a common hydrogen-bonded prereaction complex.…”
mentioning
confidence: 67%
“…Although these experiments demonstrate that 2-propenesulfenic acid is highly likely to be the peroxyl-radical scavenger in allicin-inhibited autoxidation reactions, the reason that sulfenic acids appear to be such effective antioxidants [10] is currently unclear. Since the OÀH bonddissociation enthalpy (BDE) of an H-atom donor, XOH (e.g., phenols, X = Ar), is the key thermodynamic parameter connected with the rate of reaction of XOH with peroxyl radicals, it would be desirable to compare the O À H BDE of 2-propenesulfenic acid and other sulfenic acids with the OÀH BDEs of their isoelectronic cousins, the hydroperoxides (which react with peroxyl radicals much more slowly, with rate constants of approximately 10 2 -10 3 m À1 s À1 ).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Koelewijn and Berger have shown that di-tert-butylsulfoxide decomposes at or above 60 • C to give rise to 2-methylpropanesulfenic acid and isobutylene (69), the former of which was estimated by them to react with the chain-carrying peroxyl radicals in the autoxidation of tetralin with a rate constant of ∼1 × 10 7 M −1 s −1 . 190 This high reactivity can be explained by the very low O-H BDE of sulfenic acids, an example of which has recently been determined experimentally to be 71.9 kcal mol −1 (for the persistent 9-triptycenesulfenic acid). 191 Theoretical calculations further suggest that alkanesulfenic acids react with peroxyl radicals by a barrierless PCET mechanism, thereby implying that these reactions are diffusion-controlled.…”
Section: Sulfoxidesmentioning
confidence: 99%
“…Generally, antioxidant activity of sulfur‐based compounds is explained by the oxidation of sulfur to give a sulfoxide in the initial reaction steps . Sulfoxides are considered to be the most effective antioxidants due to the formation of active radical scavenger sulfenic acid . Based on previous studies, the proposed mechanism of antioxidant activity of thiocarbonyl functionality in RAFT agents involves the following effects (see Scheme ): (1) suppression of the initiation due to formation of sulfoxides and (2) radical scavenging activity of sulfenic acid intermediate.…”
Section: Discussionmentioning
confidence: 99%